A novel automated detection system for swallowing sounds during eating and speech under everyday conditions. (26th December 2014) - Fukuike, C.; Kodama, N.; Manda, Y.; Hashimoto, Y.; Sugimoto, K.; Hirata, A.; Pan, Q.; Maeda, N.; Minagi, S.
Summary The wave analysis of swallowing sounds has been receiving attention because the recording process is easy and non‐invasive. However, up until now, an expert has been needed to visually examine the entire recorded wave to distinguish swallowing from other sounds. The purpose of this study was to establish a methodology to automatically distinguish the sound of swallowing from sound data recorded during a meal in the presence of everyday ambient sound. Seven healthy participants (mean age: 26·7 ± 1·3 years) participated in this study. A laryngeal microphone and a condenser microphone attached to the nostril were used for simultaneous recording. Recoding took place while participants were taking a meal and talking with a conversational partner. Participants were instructed to step on a foot pedal trigger switch when they swallowed, representing self‐enumeration of swallowing, and also to achieve six additional noise‐making tasks during the meal in a randomised manner. The automated analysis system correctly detected 342 out of the 352 self‐enumerated swallowing events (sensitivity: 97·2%) and 479 out of the 503 semblable wave periods of swallowing (specificity: 95·2%). In this study, the automated detection system for swallowing sounds using a nostril microphone was able to detect the swallowing event with high sensitivity and specificity even under the conditions of daily life, thus showing potential utility in the diagnosis or screening of dysphagic patients in future studies.